The Effect of Electrolyte Concentration on The Sensitivity of Low-Temperature Sensor Performance of Cu/Ni Film - Danurdara Setiamukti; Azmi Khusnani; Moh. Toifur (Science and Technology Indonesia, 2020)
Increased export-import activities on fresh food commodities in the international market led to the idea of developing new technologies in the form of cryogenic freezers using liquid nitrogen (LN2). Along with the development of preservation methods using liquid nitrogen media, we need a tool that is able to detect changes in low temperatures in LN2 storage flasks that have economic value. Therefore the purpose of this research is to make a low-temperature sensor with copper and nickel material that has an economical price. The Cu/Ni film sensor is made with an electroplating method assisted by an external magnetic field of 200 G which is installed parallel to the deposition current. The Cu/Ni film was developed by varying the concentration of the electrolyte solution. The electrolyte solution used in the deposition process consisted of a mixture of H3BO3, NiSO4, NiCl2, and H2O. Furthermore, the Cu/Ni film that was made was tested on the LN2 medium to measure its sensitivity value in response to changes in temperature. The results showed that the Cu/Ni film sensor could detect changes in the low temperature in LN2. The results of data analysis showed that the curve relationship between voltage and temperature in the sample with the 2nd concentration (C2) had the highest relationship to influence each other between the voltage and temperature variables, and the sample had the highest sensitivity value compared to the others.